Efficiency analysis of Catalonia’s construction industry pre- and post-financial crisis: a data envelopment analysis (DEA) approach - Procel, Claudette (2021)
By employing a non-parametric technique rooted in economic production theory—i.e., Data Envelopment Analysis (DEA)—this study evaluates the efficiency level of construction businesses operating in the Spanish region of Catalonia. The empirical application considers a dataset including information for more than 1000 construction businesses from Catalonia during the period 2005-2016. The empirical results reveal that the efficiency level in the Catalan construction industry drastically fell during the period of economic downturn (2009-2012).  Also, the findings show that efficiency in the industry improves after 2013; however, the speed of recovery is heterogeneous across businesses. A further analysis highlights that business size is a relevant factor explaining efficiency differences among the sampled businesses: efficiency is evidently lower in micro businesses compared to the figures reported for small and medium and large construction firms